Acute strabismus in neurological emergencies of childhood: A retrospective, single-centre study. (May 2021) - Garone, Giacomo; Ferro, Valentina; Barbato, Marta; Vanacore, Nicola; Papini, Laura; Pro, Stefano; Boni, Alessandra; Scialanga, Barbara; Nacca, Raffaella; Evangelisti, Melania; Di Nardo, Giovanni; Parisi, Pasquale; et al.
Abstract: Objectives: Acute strabismus (AS) is the most common ocular motility disorder in children. In the emergency setting evaluation, the primary concern is to exclude a potentially dangerous underlying condition, requiring immediate intervention. Our first aim was to describe the epidemiology, clinical features, and underlying causes of AS in a cohort of children presenting to the emergency department (ED). Our second aim was to identify clinical features associated with a significant risk of underlying neurological emergencies (NEs). Design and setting: Clinical records of all patients under 18 years presenting for AS to the ED of the Bambino Gesù Children's Hospital over a 10-year period were retrospectively reviewed. A logistic regression model was applied to detect predictive variables associated with a higher risk of NEs. Results: 208 patients (M:F = 1.19) were identified (0.35 cases per 1000 admission). Commonly associated symptoms included diplopia (18.3%), headache (23.1%), nausea or vomit (8.6%). Other ocular or neurological abnormalities were associated in 47.6% of patients. NEs accounted for 24.03% of all cases, mostly represented by brain tumours (8.65%). Ptosis, optic disk blurring, vomit, gait abnormalities and consciousness disorders were found to confer a significantly greater risk of an underlying NE. Conclusions: Potentially severe neurological conditions may affect almost one in four children presenting to the ED for AS. Brain malignancies are the most common dangerous cause. Presence of ptosis, papilledema, vomit, gait disorders, consciousness impairment, pupillary defects and multiple cranial nerves involvement should be considered as red flags. Highlights: Acute strabismus is a rare but alarming sign in children. Neurological emergencies affect up to 24% of children with acute strabismus. Brain malignancies are the most common emergency. Abducens nerve palsy is the most common ocular motor neuropathy. Assessing children with acute strabismus, several red flags should be considered.